Automatic instantiation of a Variable Neighborhood Descent from a Mixed Integer Programming model - Tommaso Adamo; Gianpaolo Ghiani; Emanuela Guerriero; Emanuele Manni (Operations Research Perspectives, 2017)
In this paper we describe the automatic instantiation of a Variable Neighborhood Descent procedure from a Mixed Integer Programming model. We extend a recent approach in which a single neighborhood structure is automatically designed from a Mixed Integer Programming model using a combination of automatic extraction of semantic features and automatic algorithm configuration. Computational results on four well-known combinatorial optimization problems show improvements over both a previous model-derived Variable Neighborhood Descent procedure and the approach with a single automatically-designed neighborhood structure.
Keywords: 330; Mixed Integer Programming; Variable Neighborhood Descent; Semantic features